Masculinity, Labour, and Neoliberalism Working-Class Men in International Perspective (Global Masculinities, 2018)
This book explores the ways in which neoliberal capitalism has reshaped the lives of working-class men around the world. It focuses on the effects of employment change and of new forms of governmentality on men's experiences of both public and private life. The book presents a range of international studies-from the US, UK, and Australia to Western and Northern Europe, Russia, and Nigeria-that move beyond discourses positing a 'masculinity crisis' or pathologizing working-class men. Instead, the authors look at the active ways men have dealt with forms of economic and symbolic marginalization and the barriers they have faced in doing so. While the focus of the volume is employment change, it covers a range of topics from consumption and leisure to education and family. .